The Molecular Characterization and Immunity Identification of Trichomonas vaginalis Adhesion Protein 33 (AP33) - Zhang, Zhenchao; Li, Yuhua; Wang, Shuai; Hao, Lixia; Zhu, Yunqing; Li, Haoran; Song, Xiaoxiao; Duan, Yujuan; Sang, Yuhui; Wu, Pucheng; Li, Xiangrui (Frontiers in Microbiology, 2020)
Trichomoniasis is caused by Trichomonas vaginalis (T. vaginalis), which is a widespread and serious sexually transmitted pathogen in humans. The procedure of T. vaginalis adherence to the host cell is the precondition for T. vaginalis parasitism and pathogenicity. The AP33 adhesin of T. vaginalis (TvAP33) plays a key role in the process of adhesion. In this study, the specific primers for polymerase chain reaction (PCR) were designed based on the sequence of TvAP33 (GenBank Accession No. U87098.1) to amplify the open reading frame (ORF), and the ORF was inserted into pET-32a (+) to produce recombinant TvAP33 (rTvAP33). The sequence analysis indicated that the TvAP33 gene encoded a protein of 309 amino acids with 32.53 kDa, and the protein was predicted to have a high antigen index. Western blotting assay showed rTvAP33 was successfully recognized by the sera of mice experimentally infected with T. vaginalis, while native TvAP33 in the somatic extract of T. vaginalis trophozoite was as well detected by sera from rats immunized with the rTvAP33. Immunofluorescence analysis using an antibody against rTvAP33 demonstrated that the protein was expressed and located on the surface of T. vaginalis trophozoites. The recombinant protein was emulsified in Freund’s adjuvant and used to immunize BALB/C mice three times at days 0, 14, and 28. The result of animal challenge experiments revealed the levels of IgG, IgG1 and IgG2a, and IL-4, IL-10 and IL17 among rTvAP33 vaccinated animals were integrally increased. Moreover, the rTvAP33 vaccinated animals were apparently prolonged survival time (26.45 ± 4.10) after challenge infection with this parasite. All these results indicated that TvAP33 could be used as vaccine candidate antigen to induce cell-mediated and humoral immunity.